KAJIAN LITERATUR TENTANG SISTEM REPRODUKSI MANUSIA: PERSPEKTIF BIOLOGIS, EDUKATIF, SOSIAL, DAN INOVATIF DALAM KONTEKS PENDIDIKAN DASAR - Dina Trisia; Amelia Nabilla Zahra; Anisah Raniyah Mumtazah; Fikriatunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The human reproductive system is an important component of basic science education that covers biological, psychological, social, and health aspects. This article aims to examine, the composition and operation of the reproductive systems in both men and women, as well as the puberty process, teaching challenges in primary schools, and relevant innovations in reproductive education. The discussion is strengthened with case studies and educational approaches that are in accordance with local religious and cultural values. Data are derived from student group presentations and supported by current academic literature. This review emphasizes the importance of age-appropriate, compassion-based, and value-based approaches in reproductive health education.